PENERAPAN MODEL TGT DALAM PENGEMBANGAN GAME CERDASIONAIRE UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA SD : Penelitian Research and Development (R&D) model 4D (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In this study, problems were found related to the low motivation to learn mathematics of sixth grade students of SD Negeri 010 Sepaku which was seen from the results of observations and the average initial motivation questionnaire score which showed that most students still considered mathematics as a difficult, scary, and boring subject. This study aims to develop innovative learning media in the form of a Cerdasionaire game combined with the TGT model as a solution to increase students' motivation to learn mathematics. The method used in this study is the 4D Research and Development (R&D) model which includes Define, Design, Develop, and Disseminate. Data collection techniques were carried out through observation and learning motivation questionnaires, then analyzed descriptively quantitatively. Based on the results of the study, it shows that the application of the TGT model assisted by the Cerdasionaire game has a positive impact on increasing motivation to learn mathematics as seen in the increase in the average motivation score from 17.80 in the pretest to 26.47 in the posttest or an increase of 48.69%. In addition, students' responses to the use of the Cerdasionaire game were in the very high category, with a percentage of 84.17%. This shows that the TGT model combined with the Cerdasionaire game is effective in creating a fun, competitive, and interactive learning atmosphere so that it can increase elementary school students' motivation to learn mathematics.